(untitled) (Ustozlar uchun, 2025)
This article explores the growing role of digital education in transforming teaching and learning processes in the 21st century. It highlights how online platforms, e-learning technologies, and artificial intelligence tools have influenced student engagement, educational accessibility, and personalized learning. The study emphasizes both the advantages and challenges of digital education: while technology improves global access, motivation, and interactive learning, it also creates issues related to the digital divide and reduced face-to-face communication. The article concludes that digital education is shaping a new model of learning that reflects the needs of the digital age and prepares learners for future skills.